An ionic charge-transfer dyad prepared cost-effectively from a tetrathiafulvalene carboxylate anion and a TMPyP cation. Issue 4 (6th January 2016) - Xue, Li-Jun; Huo, Peng; Li, Yan-Hong; Hou, Jin-Le; Zhu, Qin-Yu; Dai, Jie
Abstract : The assembly of a simple ionic supramolecular system would be a cost-effective way to construct donor–acceptor ensembles and the strong anion–cation interaction can enhance the charge-transfer between them. Abstract : Great progress has been made in combining a TTF moiety with a porphyrin unit by covalent bonds, but only a few examples were reported in which TTF and porphyrin assembled by noncovalent interactions. In contrast to the energy- and time-consuming synthetic procedures for the covalent system, the assembly of a non-covalent ionic system would be a cost-effective way to construct donor–acceptor ensembles. Herein a new type of ionic TTF–porphyrin dyad is obtained. A methylated tetra(4-pyridyl) porphyrin (5, 10, 15, 20-tetrakis-( N -methyl-4-pyridyl)-porphyrin, TMPyP) is selected as the cation, and TTF-bicarboxylate (L 1 ) or TTF-tetracarboxylate (L 2 ) is used as the anion. Crystal structures of two TTF-TMPyP ionic D–A compounds, TMPyP-(HL 1 )4 ·3H2 O (1 ) and TMPyP-(H2 L 2 )2 ·5H2 O (2 ), were characterized by single-crystal X-ray diffraction. The strong ionic interaction enhances the charge-transfer between the regular mixed-stacking donors and acceptors, which are investigated comprehensively by spectral, electrochemical and theoretical studies. The variation in properties between L 1 and L 2 is of great advantage to understand the influence factors for charge-transfer. The charge-transfer properties can be modulated not only by the nature of the donor or the acceptor, but also the cation–anion ratio in the salt, which shows great flexibility of the D–A ionic dyad in the design and preparation of new charge-transfer systems.